Putting Bioenergy With Carbon Capture and Storage in a Spatial Context: What Should Go Where? - Freer, Muir; Gough, Clair; Welfle, Andrew; Lea-Langton, Amanda (Frontiers in Climate, 2022)
This paper explores the implications of siting a bioenergy with carbon capture and storage (BECCS) facility to carbon emission performances for three case-study supply chains using the Carbon Navigation System (CNS) model. The three case-study supply chains are a wheat straw derived BECCS-power, a municipal solid waste derived BECCS-waste-to-energy and a sawmill residue derived BECCS-hydrogen. A BECCS facility needs to be carefully sited, taking into consideration its local low carbon infrastructure, available biomass and geography for successful deployment and achieving a favourable net-negative carbon balance. On average, across the three supply chains a 10 km shift in the siting of the BECCS facility results in an 8.6% to 13.1% increase in spatially explicit supply chain emissions. BECCS facilities producing low purity CO2 at high yields have lower spatial emissions when located within the industrial clusters, while those producing high purity CO2 at low yields perform better outside the clusters. A map is also generated identifying which of the three modelled supply chains delivers the lowest spatially explicit supply chain emission options for any given area of the UK at a 1 MtCO2/yr capture scale.